PENGARUH CITRA DESTINASI, SISTEM INFORMASI PEMASARAN DAN KEARIFAN LOKAL TERHADAP MINAT BERKUNJUNG DESTINASI WISATA GRONJONG WARITI KABUPATEN KEDIRI - Tri Wahyudi -; Pompong Budi Setiadi (Media Mahardhika, 2023)
Gronjong Wariti Tourism Destination is one of the village tours located in Mejono Village, Plemahan District, Kediri Regency, which has only been built since 2016 and has been open to the public since 2018. The uniqueness of this tourist destination is that it starts from a slum and dirty Irrigation River, which is then completely changed by the local Tourism Awareness Group (Pokdarwis) into an attractive, cheap, beautiful and rural tourist destination with various types of play rides and village-style culinary MSMEs. The purpose of this study is to determine and analyse the effect of destination image, marketing information system and local wisdom on tourist interest in visiting Gronjong Wariti tourist destination, Mejono Village, Plemahan District, Kediri Regency. The research was conducted using descriptive quantitative methods using a questionnaire as a research instrument. The number of samples analysed was 160 respondents with analysis using Partial Least Squere (PLS). The results showed that destination image, marketing information system and local wisdom have a positive and also significant influence on tourist interest in visiting tourists at the Gronjong Wariti tourist destination, Mejono Village, Plemahan District, Kediri Regency.